The first fossil Coleoptera record from the Volyn Region, Ukraine, with description of a new Glesoconomorphus (Coleoptera, Mycteridae) in syninclusion with Winterschmidtiidae (Acari) and a key to species - Dmitry Telnov (Pensoft Publishers, 2021)
Glesoconomorphus ekaterinae sp. nov. (Coleoptera, Mycteridae), representing the first ever fossil species of Coleoptera from the Volyn Region of Ukraine and the first mycterid from late Eocene Rovno amber, is described and illustrated. A key to species of the fossil mycterid genus Glesoconomorphus Alekseev, Pollock & Bukejs, 2019 is presented. The systematic position of Glesoconomorphus within Eurypinae J. Thomson, 1860 is briefly discussed. The oldest finding of phoretic Winterschmidtiidae Oudemans, 1923 mites, found on the type specimen of the new beetle species, is reported.